2018
DOI: 10.6018/analesps.34.2.289861
|View full text |Cite
|
Sign up to set email alerts
|

Relationship among sociodemographic and sport variables, exercise dependence, and burnout: a preliminary study in athletes

Abstract: Título: Relación entre variables sociodemográficas y deportivas, dependencia del ejercicio y burnout: un estudio preliminar en deportistas. Resumen: El objetivo de estudio fue conocer la prevalencia de la sintomatología de dependencia al ejercicio físico y del burnout en deportistas, así como su relación con variables demográficas y deportivas. La muestra estaba formada por 449 deportistas españoles, 320 hombres y 129 mujeres (edad: M = 19.71; DT = 6.62) a los que se le administró las versiones españolas de la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 33 publications
1
21
1
2
Order By: Relevance
“…Generally, doing frequent physical exercise is beneficial for improving sleep, both in terms of sleep latency and slow-wave sleep. These types of benefits are usually seen in adults who are middle-aged and older who have difficulties falling asleep [31].…”
Section: Introductionmentioning
confidence: 99%
“…Generally, doing frequent physical exercise is beneficial for improving sleep, both in terms of sleep latency and slow-wave sleep. These types of benefits are usually seen in adults who are middle-aged and older who have difficulties falling asleep [31].…”
Section: Introductionmentioning
confidence: 99%
“…Exercise dependence is an infrequent pathology (Morris et al, 1990). In university students it represents a low proportion in the same lines as recent studies (Reche et al, 2015;Reche et al, 2018). Most exercise dependence cases are in women, athletes below the age of 20, those with more weekly training sessions and in athletes with more sport experience.…”
Section: Discussionmentioning
confidence: 66%
“…Having described the statements in the previous paragraphs, it is necessary to specify that taking into account the burnout of the athlete as a result of training overload is to consider a multidimensional phenomenon where different factors come into play, such as emotional and physical fatigue, decreased achievement, and sport devaluation (Goodger et al, 2007a;Reche et al, 2018). Early studies on burnout defined the concept within the framework of feelings of failure and exhaustion in the face of excessive demands on energy, strength, and personal resources (Carlin and Garcés de los Fayos Ruiz, 2010).…”
Section: Burnout Syndromementioning
confidence: 99%
“…Thus, in the last decade, numerous studies can be found in which the authors measure burnout syndrome in different collective sports modalities such as football (Lopes Verardi et al, 2015), rugby Eklund, 2005, 2006), and volleyball (Vieira et al, 2013). On the other hand, research on burnout in individual sports such as athletics (Reche et al, 2018), swimming (Larson et al, 2019), tennis and table tennis (Goodger et al, 2007b;Martinent et al, 2014Martinent et al, , 2020, or olympic wrestling (Gil et al, 2015) stand out.…”
Section: Burnout Syndromementioning
confidence: 99%